Kajian Ekologi dan Sosial Ekonomi Mangrove dalam Mendukung Pemanfaatan Kawasan Pesisir Berkelanjutan di Kabupaten Merauke - Nova Suryawati Monika; Sunarni Sunarni; Sajriawati Sajriawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to examine the ecological and socio-economic aspects of mangrove utilization in Nasem Village, Merauke Regency, Papua Selatan. The ecological assessment included mangrove species composition, regeneration potential, health status, and Importance Value Index (INP). Socio-economic data were collected through questionnaires and focus group discussions with 30 respondents. The results showed that Avicennia marina had good regeneration potential and dominated the community with the highest INP (1.13), while Avicennia alba was categorized as new regeneration with a low INP (0.31). The health status of both species was classified as rare/damaged according to national standards, indicating the need for restoration. From a socio-economic perspective, 90% of respondents utilized mangroves for firewood and fisheries, and 95% stated that mangroves significantly contributed to household income, although 83% earned less than IDR 1,000,000 per month. Most respondents (85%) recognized the ecological functions of mangroves, but anthropogenic pressures such as sand mining remained major threats. These findings highlight the urgent need for community-based mangrove management that integrates ecological restoration with sustainable economic development. The study provides scientific evidence to support policy recommendations for sustainable coastal zone management in Merauke.